A novel cause of DKC1‐related bone marrow failure: Partial deletion of the 3′ untranslated region. Issue 2 (26th January 2021) - Arthur, Jonathan W.; Pickett, Hilda A.; Barbaro, Pasquale M.; Kilo, Tatjana; Vasireddy, Raja S.; Beilharz, Traude H.; Powell, David R.; Hackett, Emma L.; Bennetts, Bruce; Curtin, Julie A.; Jones, Kristi; Christodoulou, John; et al.
Abstract: Telomere biology disorders (TBDs), including dyskeratosis congenita (DC), are a group of rare inherited diseases characterized by very short telomeres. Mutations in the components of the enzyme telomerase can lead to insufficient telomere maintenance in hematopoietic stem cells, resulting in the bone marrow failure that is characteristic of these disorders. While an increasing number of genes are being linked to TBDs, the causative mutation remains unidentified in 30‐40% of patients with DC. There is therefore a need for whole genome sequencing (WGS) in these families to identify novel genes, or mutations in regulatory regions of known disease‐causing genes. Here we describe a family in which a partial deletion of the 3′ untranslated region (3′ UTR) of DKC1, encoding the protein dyskerin, was identified by WGS, despite being missed by whole exome sequencing. The deletion segregated with disease across the family and resulted in reduced levels of DKC1 mRNA in the proband. We demonstrate that the DKC1 3′ UTR contains two polyadenylation signals, both of which were removed by this deletion, likely causing mRNA instability. Consistent with the major function of dyskerin in stabilization of the RNA subunit of telomerase, hTR, the level of hTR was also reduced in the proband, providing a molecular basis for his very short telomeres. This study demonstrates that the terminal region of the 3′ UTR of the DKC1 gene is essential for gene function and illustrates the importance of analyzing regulatory regions of the genome for molecular diagnosis of inherited disease.